The pricing of global and domestic initial public offerings by US companies - Wu, Congsheng; Kwok, Chuck C.Y. (Journal of Banking & Finance, 2003)
This study examines the pricing of global initial public offerings made by US companies as compared to purely domestic offerings. We find that global participation can significantly reduce underpricing by about four percentage points. Moreover, the degree of underpricing declines as larger proportions of shares are allocated to foreign investors. Our results suggest that US companies time their global offerings when foreign demand for US shares is high. There is also evidence that global offerings alleviate the downward pricing pressure associated with new share offerings.